Lissencephaly Type III Syndrome - J Gordon Millichap (Pediatric Neurology Briefs, 1996)
Arthrogryposis multiplex congenita (AMC), called fetal akinesia sequence (FAS) in this study of 5 lethal cases, was associated with a distinctive neuropathological pattern, named type III lissencephaly syndrome, as reported from the Hopital Henri Mondor, Creteil, and the Hopitals Port Royal and Saint Antoine, Paris, France.